A case of Cryptococcus gattii infection in South Carolina: A possible challenge to known endemicity. (2021) - Summers, Robert P.; Abel, William F.; Sessions, William S.; Polley, Eric M.; Shirley, Rhett M.; Schnee, Amanda E.
Abstract: In the United States, C. gattii is considered to be endemic to the Pacific Northwest and although uncommon, additional cases have been documented in other regions including the Southeastern United States. While it has been hypothesized in the past that C. gattii may be endemic to the Southeastern United States, there remains a paucity of evidence. Here, we present a patient with no history of HIV/AIDS and no organ transplant and document the course of his disease and presentation. There were no adverse long-term neurological outcomes in this patient and the combination of steroid use, antifungal agents, and cerebrospinal fluid drainage resulted in his discharge from the hospital after 12 days. This patient's subacute presentation with vague neurological symptoms highlights the importance of understanding the treatment of rare causes of meningitis.